A231 ENDOSCOPY TRAINEES ARE ABLE TO ACCURATELY SELF-ASSESS PROCEDURAL SKILLS. (15th March 2019) - Cookson, T A; Beilman, C L; Kohansal, A R; Sadowski, D; Peerani, F; Bistritz, L; Zepeda-Gomez, S; Kroeker, K
Abstract: Background: Trainees in gastrointestinal endoscopy (GIE) learn at differing rates and may not be able to accurately self-assess their endoscopic skills. A transition to competence-based medical education (CBME) in Canada has brought direct evaluation to the forefront. The Direct Observation of Procedural Skills (DOPS) is a tool used by physicians to assess trainee skill level in GIE procedures, including: colonoscopies (COL), flexible sigmoidoscopies (SIG), and gastroscopies (GASTRO). To validate the reliability of GI resident self-assessment in endoscopy, the Ottawa Surgical Competency Operating Room Evaluation (O-SCORE) is used for CBME assessment. Aims: To evaluate the self-assessment skills of trainees in endoscopy as compared to staff assessment using the O-SCORE for DOPS evaluation of GI procedures. Methods: Staff and trainees completed an assessment evaluating the skill level demonstrated by the trainee in GIE. Difficulty was evaluated on a 3-level scale: easy, moderate, complicated. Procedural skills were evaluated using a 5-level O-SCORE: (1) the staff had to do, (2) the staff had to talk the trainee through, (3) the staff had to prompt the trainee from time to time, (4) the staff needed to be in the room just in case, (5) the staff did not need to be there. Numerical data are presented as a mean and compared using Wilcoxon Signed-Rank test. Significance is evaluated at α=0.05. Results: There were 10 trainees (33.3% female) and 16 staff recruited. Data was collected for 43 COLs/SIGs and 42 GASTROs. There were no significant differences in the mean trainee scores compared to the staff in any of the assessments, except for evaluating difficulty of COLs/SIGs; in which, staff rated them more difficult (2.05) than trainee (1.79) scores (p=0.008). Table 1 shows a summary of the results for each trainee. Conclusions: As a whole, endoscopy trainees are able to accurately self-assess procedural skills in endoscopy. However, individual ability to self-evaluate varies amongst trainees. Funding Agencies: None